El viaje de la ciencia ficción argentina a los confines del espacio interior - Martín Felipe Castagnet (Cuadernos LIRICO)
In the introduction to a 1978 science fiction anthology, Elvio Gandolfo wrote : “Argentine science fiction does not exist”. Today, Argentine science fiction is close to having its own constellation in the literary firmament. In the time elapsed since Gandolfo’s introduction, changes have taken place in the genre as well as in the Argentine publishing world, that have affected the ways in which that production circulates. In this article, we will try to determine what kinds of changes have occurred in the genre, and in which publishing context. This approach concerns publishing practices but it does not exclude, as it is too often the case, the analysis of literary texts themselves. We will also see how the peritext, authorial and editorial, determines genres and, in many cases, even prompts their emergence.